PROCEEDINGS : The 16th AAAP Congress SUSTAINABLE LIVESTOCK PRODUCTION IN THE PRESPECTIVE OF FOOD SECURITY, POLICY, GENETIC RESOURCES, AND CLIMATE CHANGE - Susmiati, Trini; Putro, Prabowo Purwono; Pangestiningsih, Triwahyu; Widayanti, Rini; Airin, Claude Mona (Fakultas Kedokteran Hewan Universitas Gadjah Mada, 2014)
Cholesterol oxidation process could happen in aorta or artery. The purpose of this research is to investigate the mechanism and getting the effective dosage of curcuminoid turmeric extract in preventing the initial process of pathogenesis atherosclerosis in vivo. There were 30 rats divided into 6 groups. Curcuminoid extract was isolated from tumeric using maseration and methanol method, and then the extraction was tested to the rats with atherosclerosis. The concentration of low density lipoprotein (LDL) was determinedusing cholesterol kit. Coloring with haemathociline (HE) was used to investigate the atherosclerotic in aorta and coronaria arteries. Curcuminoid was obtainedfrom the extraction oftumeric(1,2% from 10 kg of tumeric). The result of LDL plasma cholesterol average count after 4-wk treatment for each groups were: group A: 94,29-151,11 mg /di,B: 102,86- 155,55 mg /dl, C:125,71- 173,33 mg /di,D:144,28- 164,44 mg /dl,E :105,72- 155,55 mg /dl, and group F: 102,85- 138,8 mg /dl. The statistical test showed the increase of cholesterol (P<0,05),as well as LDL cholesterol: Group A: 87,24-138,67 mg/dl,B: 94,99-140,59 mg /dl, C: 118, 24-160,57 mg /dl, D: 118,22- 157,57 mg /dl, E :105,58-139,72 mg /dl, and F: 99,1-119,74 mg /dl (P<0,05). Theatherosclerosisplagueswere shown by the smooth muscle cell, macrophag cell accumulation, fat cells, and fat scratches asthehistological coloring results ofaorta and coronaria artery.It can be concluded that curcuminoid tumeric extract was still disable to prefent therosclerosis Atherosclerosis, LDL Cholesterol, curkcuminoid tumeric extract, aorta,coronariaartery